Upaya Peningkatan Penguasaan Guru SD dalam Penelitian Tindakan Kelas dan Penulisan Karya Tulis Ilmiah Melalui Pelatihan - Nilakusmawati, D.P.E.; Sari, K.; Puspawati, N.M. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi, 2016)
Overall this IbM program aimed to improve the competence of the teachers in cluster V Karangasem district in Classroom Action Research (CAR) and writing scientific articles through training and mentoring efforts. The purpose of this study was to determine the level of mastery of elementary School teachers about CAR and writing scientific articles through training efforts. The training was conducted over three days, discussed the subjects: Basic Concepts of CAR; Steps of CAR; Designing CAR; CAR report; and Writing Scientific Articles. Participants are elementary school teachers from seven schools in Cluster V Karangasem district, with a total of 33 participants. The design of this research is one group pretest-posttest. Pre-test and post-test consists of ten questions about CAR and ten questions about the scientific articles. To determine whether the increased mastery of teachers on CAR and scientific papers after the training is given, then the t-test with significance level of 5% are applied. The results of the analysis showed that there is a significant improvement of teachers mastery after the procurement trained. The average teachers mastery on pre-test is 43.64 and post-test is 60.15. By Providing training, increase the mastery of teachers about CAR and scientific articles about 37.85 percent.
Keywords: Classroom Action Research, CAR, scientific articles, scientific papers, teachers mastery